La creación del espacio trágico en la obra de Gabriel García Márquez: Una lectura sofoclea - Reig Calpe, Montserrat (Universidad Nacional de La Plata. Facultad de Humanidades y Ciencias de la Educación. Centro de Estudios Helénicos, 2011)
The influence of Sophocles, particularly of his Theban tragedies, on García Márquez's work can be perceived at several different levels: in the construction of the plot, in the conception of the Tyrant character, in the violence and fate themes, and of course in the treatment of time and space. The focus of this paper lies on the construction of space in García Márquez's work through two opposed elements originating in his reading of Sophoclean tragedy: the genos, symbolic of a closed space, linked to a "round" time, which is the space of the narration; and the polis, an open, remote space, in which the time of History unfolds. This dichotomy is analyzed in several works by García Márquez, with special attention paid to Edipo alcalde. Thus, the tragic conflict of civil discord finds its reflection in a single, claustrophobic, and corrupted space